2000
DOI: 10.1139/f00-118
|View full text |Cite
|
Sign up to set email alerts
|

Interrenal metallothionein and cortisol secretion in relation to Cd, Cu, and Zn exposure in yellow perch, Perca flavescens, from Abitibi lakes

Abstract: The concentrations of Zn, Cu, and Cd in the interrenal tissue and liver of yellow perch, Perca flavescens, sampled in six lakes in the mining region of Abitibi (Quebec) revealed a gradient of contamination: reference lakes, intermediate-contaminated lakes, and highly contaminated lakes. Interrenal and hepatic metallothionein concentrations followed a similar gradient, and there was a strong relationship between metallothionein and total metal (Zn + Cu + Cd) content in the liver and Cu + Cd content in the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 41 publications
7
58
1
Order By: Relevance
“…The water Cu concentrations used in this study were environmentally relevant and did result in accumulation of Cu in fish tissues. Moreover, Cu concentrations in livers of trout exposed to the higher concentration (80 g/l) were similar to levels reported by Laflamme et al (2000) in perch from field studies in the mining area of Abitibi, Qc. Similar to other laboratory and field studies, liver was the principal organ of Cu accumulation, followed by other tissues (McGeer et al, 2000b;Audet and Couture, 2003;Lévesque et al, 2003;Giguere et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The water Cu concentrations used in this study were environmentally relevant and did result in accumulation of Cu in fish tissues. Moreover, Cu concentrations in livers of trout exposed to the higher concentration (80 g/l) were similar to levels reported by Laflamme et al (2000) in perch from field studies in the mining area of Abitibi, Qc. Similar to other laboratory and field studies, liver was the principal organ of Cu accumulation, followed by other tissues (McGeer et al, 2000b;Audet and Couture, 2003;Lévesque et al, 2003;Giguere et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Concentration of Cu were measured by inductively coupled plasma atomic emission spectrophotometry (ICP-AES) in water, and in kidney, interrenal tissue and liver, using tissue homogenates corresponding to 100 mg dry weight, as described previously by Laflamme et al (2000). A mass of 1 g/g dry weight corresponds to approximately 0.29 g/g wet weight.…”
Section: Analyses Of Cumentioning
confidence: 99%
“…However, Cd and Pb are of serious concern and adequate control of their sources is paramount because of their negative impact on biotics and the ecosystem at large. Pb and Cd affect metallothionein, a cystine rich, low-molecularweight, metal-binding protein (Perceval et al, 2002) and hormonal activity in living organisms (Laflamme et al, 2000). Pb has caused anaemia, brain damage, anorexia, renal failure, mental deficiency, vomiting and even death in human (Bulut and Baysal, 2006;Low et al, 2001) even at trace levels lower than the observed concentration in this study.…”
Section: Assessment Of Individual Metal Contaminant and Transfer Factormentioning
confidence: 46%
“…Several studies have reported that yellow perch tissue metal concentrations are influenced by environmental contamination (Brodeur et al 1997;Laflamme et al 2000;Levesque et al 2002;Campbell et al 2003;Couture and Rajotte 2003;Pyle et al 2005;Couture et al 2008a). A number of reports also indicate that metal-contaminated wild yellow perch suffer a range of metabolic and energetic impairments, including an impaired cortisol stress response (Hontela et al 1996;Brodeur et al 1997;Laflamme et al 2000;Lacroix and Hontela 2004), bioenergetics (Sherwood et al …”
Section: Introductionmentioning
confidence: 99%
“…A number of reports also indicate that metal-contaminated wild yellow perch suffer a range of metabolic and energetic impairments, including an impaired cortisol stress response (Hontela et al 1996;Brodeur et al 1997;Laflamme et al 2000;Lacroix and Hontela 2004), bioenergetics (Sherwood et al …”
Section: Introductionmentioning
confidence: 99%